2021
DOI: 10.1007/s12028-021-01282-5
|View full text |Cite|
|
Sign up to set email alerts
|

Pain Trajectories Following Subarachnoid Hemorrhage are Associated with Continued Opioid Use at Outpatient Follow-up

Abstract: Background Subarachnoid hemorrhage (SAH) is characterized by the worst headache of life and associated with long-term opioid use. Discrete pain trajectories predict chronic opioid use following other etiologies of acute pain, but it is unknown whether they exist following SAH. If discrete pain trajectories following SAH exist, it is uncertain whether they predict long-term opioid use. We sought to characterize pain trajectories after SAH and determine whether they are associated with persistent op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Research on novel treatment options for HASH is greatly needed. An effective treatment strategy for HASH likely needs to be multifaceted considering complex pathophysiology, individual pain perception and pain trajectories (10). Although exact mechanism of HASH has not been elucidated, current evidence suggests that blood in the subarachnoid space in the brain and neck can mechanically stretch and irritate trigeminovascular and greater occipital afferent neurons resulting in headache and meningismus (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on novel treatment options for HASH is greatly needed. An effective treatment strategy for HASH likely needs to be multifaceted considering complex pathophysiology, individual pain perception and pain trajectories (10). Although exact mechanism of HASH has not been elucidated, current evidence suggests that blood in the subarachnoid space in the brain and neck can mechanically stretch and irritate trigeminovascular and greater occipital afferent neurons resulting in headache and meningismus (16).…”
Section: Discussionmentioning
confidence: 99%
“…All patients were followed up at 1 week after enrollment, so we were able to show there was still benefit at that time point. Importantly, there is growing research that patients with HASH follow discrete pain trajectories ( 10 ), and pain trajectories can predict generation of chronic pain ( 9 , 33 ). In our preliminary study, we found that PNB appeared to alter this trajectory immediately after administration, therefore it is plausible that it may alter and development of chronic HASH in some patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of data-proven effective headache management strategies, lack of updated guidelines for such management, and incomplete understanding of trajectories of post-SAH headache [17,18], we hypothesized that signi cant practice variability exists in the management of acute post-SAH headaches in the critical care setting. The objective of this study is to examine the variety of different approaches to manage headaches in non-traumatic SAH patients during hospitalization and at discharge from the hospital with an emphasis on characterizing opioid administration and spanning international practice.…”
Section: Introductionmentioning
confidence: 99%
“…Among soldiers returning from active duty who have a TBI diagnosis, nearly 60% are prescribed an opioid during the postdeployment year 21 22. In a study of patients with acute neurological injury suffering from aneurysmal subarachnoid haemorrhage, opioid use was associated with discrete pain trajectories, pain burden and craniotomy 23 24. Opioid sparing during hospitalisations with acute pain is an important component of addressing the current opioid epidemic 25.…”
Section: Introductionmentioning
confidence: 99%